Manaqib Writing in the Circle of the Tariqa Qadiriyya wa Naqsyabandiyyah: A Study on Muhammad Siddiq al-Salihi’s Nayl al-Amani - Widiyanto, Asfa (Center for Research and Development of Religious Literature and Heritage, 2015)
The manaqib of ‘Abd al-Qadir al-Jilani is of particular importance in the circle of the Tariqa Qadiriyya wa Naqsyabandiyyah (TQN). Some leaders of the TQN have done their best to give a translation and explanation of this manaqib. For instance, Muhammad Siddiq al-Salihi composed a work titled Nayl al-amānī fī dhikr manaqib al-quṭb al-rabbānī sayyidinā al-shaykh ‘Abd al-Qādir al-Jīlanī. Another leader, Muslih ibn ‘Abd al-Rahman al-Maraqi, wrote a treatise titled al-Nūr al-burhānī fī tarjamat al-lujayn al-dānī fī dhikr nubdhah min manaqib al-shaykh ‘Abd al-Qādir al-Jīlanī. The TQN master Nawawi Siddiq al-Zarkashi wrote a treatise titled Fuyuḍāt al-rabbānī fīkayfīyāt qirā’at manaqib sulṭān al-awliyā’ al-shaykh muḥyī al-dīn ‘Abd al-Qādir al-Jīlanī. This paper will pay particular attention to the Nayl al-amani, since this work is relatively unknown in Indonesian academia. This book is written in standard Arabic, something which is nowadays rare in the Pesantren and tariqa scholarship. This book is read during the monthly communal ritual of the TQN in the Pesantren Manba’ al-Falah, Dawe, Kudus, Central Java. This paper strives to unravel the narratives of hagiography in Nayl al-amani and also highlight the uniqueness of Nayl al-amani, most particularly in comparison with the two manaqib writings in the circle of the TQN in Central Java.